Poly(A) Polymerase Activity in Reovirus - Stoltzfus, C. M. (1974)
An enzymatic activity which synthesized oligo(A) in vitro was found in highly purified reovirus. The poly(A) polymerase activity was dependent on Mn(2+) and utilized only ATP, whereas the virion-associated RNA polymerase required all four ribonucleoside triphosphates and Mg(2+). Oligo(A) synthesis was demonstrated with complete virions and infectious subviral particles derived from virus by limited chymotrypsin digestion but not with cores, a product of extensive chymotrypsin digestion of virus. The enzymatic product and the oligo(A) from purified virions were isolated by binding to oligo(dT)-cellulose columns. Most of the in vitro product was similar in size and structure to the oligo(A) from purified virions by the criteria of gel electrophoresis, DEAE-cellulose chromatography, end-group analysis, and sensitivity to RNase. The evidence suggests that oligo(A) synthesis is mediated by the poly(A) polymerase during a late step in viral morphogenesis and may result from an alternative activity of the virion-associated transcriptase.